Judge Not the Play Before the Play Is Done: The Role of Creative Play in the Treatment of a Child with a History of Congenital Impairment. Issue 1 (1st January 2019) - Mirkin, Marina
ABSTRACT: This paper explores the organizing effect of a relatively minor congenital medical condition on the development of an 8-year-old girl; the role of creative play in the integration of what she experienced as traumatic; and finally, the role of play as facilitating her progressive development. Despite full recovery from her medical condition, the patient's limitations in mobility between the ages of 1 and 4 profoundly affected her image of herself and her sense of self-worth. The central character in her symbolic play also suffered from mobility restrictions and the changes in the doll's capacity to use her legs closely corresponded to the changes in the patient's self-representation. Detailed clinical material of the nine-year-long analysis focuses on the development-promoting role of creative play. It also features the transition from imaginative play to direct discourse, and the course of the successful termination of her analytic treatment. The interpretive work involving the patient's neurotic conflicts is highlighted within this context.